Further Evidence on Convergence across Italian Regions - Patrizia Margani; Roberto Ricciuti (European Regional Science Association (ERSA), 2001)
In the last decade the issue of convergence across states and regions has received a great deal of attention both on the theoretical and empirical ground. On the empirical ground different specifications lead to different results and their robustness is also questioned. We review both neoclassical and endogenous growth theories and the evidence on international and Italian data. We use a methodology that enhances the power of the estimates proposed by Evans and Karras (Journal of Monetary Economics, 1996) that uses panel data and test for their stochastic properties. Data cover the time-span 1951-1998. We find evidence of conditional convergence.
Keywords: 330